The new semi-analytic code GalICS 2.0 – reproducing the galaxy stellar mass function and the Tully–Fisher relation simultaneously - Cattaneo, A; Blaizot, J; Devriendt, J; Mamon, G; Tollet, E; Dekel, A; Guiderdoni, B; Kucukbas, M; Thob, A (Oxford University Press, 2017)
GalICS 2.0 is a new semianalytic code to model the formation and evolution of galaxies in a cosmological context. N-body simulations based on a Planck cosmology are used to construct halo merger trees, track subhaloes, compute spins and measure concentrations. The accretion of gas onto galaxies and the morphological evolution of galaxies are modelled with prescriptions derived from hydrodynamic simulations. Star formation and stellar feedback are described with phenomenological models (as in other semianalytic codes). GalICS 2.0 computes rotation speeds from the gravitational potential of the dark matter, the disc and the central bulge. As the rotation speed depends not only on the virial velocity but also on the ratio of baryons to dark matter within a galaxy, our calculation predicts a different Tully-Fisher relation from models in which vrot ∝ vvir. This is why GalICS 2.0 is able to reproduce the galaxy stellar mass function and the Tully-Fisher relation simultaneously. Our results are also in agreement with halo masses from weak lensing and satellite kinematics, gas fractions, the relation between star formation rate (SFR) and stellar mass, the evolution of the cosmic SFR density, bulge-to-disc ratios, disc sizes and the Faber-Jackson relation.